Assessing Managers and Staff Perceptions of the Benefits of Implementing an Electronic Health Record (EHR) System: A Case Study of the Ghana Atomic and Energy Commission Clinic. - Amponsah, J. (University of Ghana, 2018)
Health Information Technologies such as Electronic Health Records (EHRs) is considered by health care professionals, consumers and policy makers to be fundamental in transforming the health care industry. Given the complex nature of the health care industry, the limitations of using paper-based medical records are obvious, hence a transition of traditional paper-based medical records to electronic health recording system. EHR is known to reduce loads of medical records keeping, quality of care and improved health workers productivity and clients-provider interaction. The situation was not different at the Ghana Atomic Energy Commission Clinic (GAECC) where this study was conducted after three (3) years of implementing an EHR. The study assessed managers and staffs‘ perception on the expected benefits, realized benefits and the challenges encountered during and after implementing the EHR. Quantitative method was used to achieve the objectives which used structured questionnaire as the main data gathering tool. Respondents were selected based on those who had access or used the EHR system. The level of perception for benefits was assessed based on the following indicators, Quality of care, Evidence-based & patient safety, Communication and coordination of care, Efficiency, Patient experience and involvement in care and Usefulness of system. Descriptive univariate analysis was used to describe the demographic characteristics of the respondents. Whereas t-test and Oneway Anova was done to determine the difference between the perception of expected benefits and the benefits that were realized after all the dependent variables were rated and the average means of all created composite variables were calculated. The results showed that staff stakeholders had high perceptions of EHR to yield benefits like Quality of Care, Communication, Co-ordination of care, Efficiency and Patient Experience and Involvement.
MSc.
Keywords: Electronic Health Record; Ghana Atomic; Energy Commission Clinic